P1371HEART FAILURE HOSPITALISATIONS IN THE PIVOTAL TRIAL OF IV IRON IN HAEMODIALYSIS PATIENTS: A PRE-SPECIFIED SECONDARY ANALYSIS. (6th June 2020) - Jhund, Pardeep; Petrie, Mark; Robertson, Michele; Mark, Patrick; Macdonald, Michael; Connolly, Eugene; White, Claire; Reid, Chante; Anker, Stefan D; Bhandari, Sunil; Farrington, Kenneth; Kalra, Philip A; et al.
Abstract: Background and Aims: Heart failure (HF) is a common and potentially deadly complication in patients receiving haemodialysis which is difficult to diagnose and treat. The impact of a proactive high-dose strategy compared to a reactive low-dose strategy of IV iron administration was investigated in the PIVOTAL randomised trial in incident haemodialysis patients, with fatal HF and HF hospitalisation being components of the composite primary cardiovascular endpoint as well as a pre-specified key secondary event. The aim of this analysis was to examine the effect of a proactive high-dose strategy compared to a reactive lower dose strategy on HF events in patients recruited to PIVOTAL. Method: As with the primary composite cardiovascular endpoint, HF hospitalisations in PIVOTAL were recorded prospectively via an electronic database, and events were then adjudicated by a blinded Endpoint Adjudication Committee. The time-to-event analyses of the primary, secondary and post hoc outcomes were performed in the intention-to-treat population using Cox proportional hazards regression, with treatment group as the only explanatory variable. The Kaplan–Meier method was used to estimate event rates. Both fatal and non-fatal HF events were analysed as time to first event, and a recurrent event analysis was also performed for non-fatal events. Results: Overall, 2141 participants were followed for a median of 2.1 years. A first fatal or non-fatal HF event occurred in 51 of 1093 patients (4.7%) in the high-dose iron group and in 70 of 1048 patients (6.7%) in the low-dose iron group (hazard ratio 0.66, 95% confidence interval 0.46 to 0.94; P<0.001) (Figure). There was a total of 63 HF events (including first and recurrent events) in the high-dose iron group and 98 in the low-dose iron group, giving a rate ratio of 0.59 (0.40-0.87); p=0.0084. A history of HF and diabetes were independent predictors of a heart failure event. Conclusion: Compared with a low-dose regimen, high-dose intravenous iron decreased the occurrence of first and recurrent heart failure events in incident patients undergoing haemodialysis, with large relative and absolute risk reductions.